Peran Whistleblowing System Dalam Pencegahan Kecurangan Dana Organisasi Kemahasiswaan (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the implementation of the whystleblowing system in PTN student organizations in Central Java Province, the level of disclosure of student fund fraud cases found with the whystleblowing system, and to find out how to build an effective whystleblowing system in student organizations. This research uses primary data with qualitative analysis techniques using a descriptive approach. The implementation of the whistleblowing system in PTN student organizations in Central Java Province not only aims to detect and overcome potential ethical violations, but also to increase the trust and integrity of the entire campus community. The level of fraud revealed through the Whistleblowing System can vary, depending on factors such as the size of the institution, internal policies, and the level of awareness of organizational staff about the importance of reporting fraud. An effective whistleblowing system in the context of student organizations involves a series of strategic steps and attention to key elements that include developing a system that not only facilitates safe and anonymous reporting, but also encourages a culture of transparency, integrity and fairness among organizational members.